Risk Factors for Congenital Anomalies in Neonatal Intensive Care Unit in Baghdad City (Medico Legal Update, 2020)
Study Aim: to assess the possible risk factors of congenital anomalies and its patterns in Baghdad city.Methodology: a cross sectional design carried out in NICU at two main governmental pediatric hospitals in Baghdad city. Sixteen newborns medically diagnosed with congenital anomalies were involved at time of data collection. The instrument of the study concerned with newborns and their mothers’ data related to the possible risk factors that may lead to congenital anomalies. The data were analyzed by using SPSS program.Results: the result of the study revealed that (60%) of neonate were boys, and (48.3%) was preterm. For systematic body anomalies (30%) documented for gastrointestinal system, (26.7%) cardiovascular and (23.3%) central nervous system. The result also showed (66.7%) of mother > 34 years, (61.7%) with BMI ? 30, (56.6%) with hypertension, (63.3%) anaemic, (60%) self medication, (80%) have positive family history, (58.3%) lived near mobile station, (56.6%) consanguinity, (70%) did not take folic acid, (65%) with low socioeconomic status.Conclusion: most common anomalies were gastrointestinal, cardiovascular, and central nervous system. Elder mothers, increased BMI, chronic diseases, consanguinity, positive family history, and low socioeconomic status were related to increased incidence of congenital anomalies.Recommendation: increased health awareness about the antenatal check up, concern about neonatal exam for early diagnosis, and folic acid supplements during pregnancy period.